2014
DOI: 10.1371/journal.pone.0089199
|View full text |Cite
|
Sign up to set email alerts
|

The Antidepressant Trans-2-Phenylcyclopropylamine Protects Mice from High-Fat-Diet-Induced Obesity

Abstract: Mice treated with the antidepressant trans-2-phenylcyclopropylamine (2-PCPA) were protected against diet-induced-obesity, and adiposity was reversed in pre-established diet-induced obese mice. Contrary to a recent report that inhibition of lysine-specific demethylase-1 by 2-PCPA results in increased energy expenditure, long-term 2-PCPA treatment had no such effect but its protection against obesity was associated with increased spontaneous locomotor activity, Moreover, pair feeding to assure equal caloric inta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Nevertheless, these results could be interpreted in a different light, since: 1) ephedrine is currently banned in view of its amphetamine-like structure and related adverse effects; and 2) tranylcypromine is not a simple MAOI, being now recognized as an SSAO [33] and LSD inhibitor [11,12]. Furthermore, recent studies have confirmed an anti-obesity effect for tranylcypromine even in mice invalidated for the uncoupling protein-1 (UCP1) involved in non-shivering thermogenesis and in beiging of WAT [26]. Thus, these recent findings indicate that tranylcypromine not only increases the basal metabolic rate, but it also increases spontaneous locomotor activity and decreases food intake.…”
Section: Past and Present Observations Of Amine Oxidase Inhibitor mentioning
confidence: 99%
“…Nevertheless, these results could be interpreted in a different light, since: 1) ephedrine is currently banned in view of its amphetamine-like structure and related adverse effects; and 2) tranylcypromine is not a simple MAOI, being now recognized as an SSAO [33] and LSD inhibitor [11,12]. Furthermore, recent studies have confirmed an anti-obesity effect for tranylcypromine even in mice invalidated for the uncoupling protein-1 (UCP1) involved in non-shivering thermogenesis and in beiging of WAT [26]. Thus, these recent findings indicate that tranylcypromine not only increases the basal metabolic rate, but it also increases spontaneous locomotor activity and decreases food intake.…”
Section: Past and Present Observations Of Amine Oxidase Inhibitor mentioning
confidence: 99%
“…The genetic inhibition of 5-HT synthesis in the brainstem decreases food intake and body weight in ob/ob mice and the wild-type mice [ 12 ]. In addition, the pharmacologic inhibition of 5-HT synthesis in the brainstem induced by treatment with a high dose PCPA (500 mg/kg) or trans-2 PCPA decreases body weight and food intake in C57BL6J mice, db/db mice [ 2 ], and high-fat diet-induced obesity [ 13 ]. Thus, the decrease in central 5-HT leads to the decrease in body weight and food intake in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic inhibition of 5-HT synthesis in the brainstem decreases food intake and body weight in ob/ob mice and wild-type mice [2]. In addition, pharmacologic inhibition of 5-HT synthesis in the brainstem induced by treatment with a high dose of p-chlorophenylalanine (PCPA) (500 mg/kg) or trans-2 PCPA decreases body weight and food intake in C57BL6J mice, db/db mice [4], and high-fat-diet-induced obesity [5]. Thus, depletion of brainstem-derived 5-HT leads to decreases in body weight and energy intake in mice.…”
mentioning
confidence: 99%